2016
DOI: 10.1111/joa.12496
|View full text |Cite
|
Sign up to set email alerts
|

The expression of tenascin‐C and tenascin‐W in human ossicles

Abstract: The ossicles of the middle ear (the malleus, incus and stapes) transmit forces resulting from vibrations of the tympanic membrane to the cochlea where they are coded as sound. Hearing loss can result from diseases such as rheumatoid arthritis (RA) that affect the joints between the ossicles or degenerative processes like otosclerosis that lead to ankylosis of the footplate of the stapes in the oval window of the cochlea. In this study, immunohistochemistry was used to determine if the extracellular matrix glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…To date, the only evidence of tenascin-W expression in the central nervous system comes from Neidhardt et al (4). Others found that the primary sites of expression are developing palate, bone and smooth muscle, certain stem cell niches, and in adult kidney, spleen, and periosteum (7)(8)(9)(10)(11)(12). The absence of significant tenascin-W expression in brain parenchyme was confirmed by the tissue-based map of the human proteome published by Uhleń at el.…”
Section: The Discovery and Expression Of Tenascin-wmentioning
confidence: 94%
“…To date, the only evidence of tenascin-W expression in the central nervous system comes from Neidhardt et al (4). Others found that the primary sites of expression are developing palate, bone and smooth muscle, certain stem cell niches, and in adult kidney, spleen, and periosteum (7)(8)(9)(10)(11)(12). The absence of significant tenascin-W expression in brain parenchyme was confirmed by the tissue-based map of the human proteome published by Uhleń at el.…”
Section: The Discovery and Expression Of Tenascin-wmentioning
confidence: 94%
“…In the adult mouse tenascin-W expression is observed in periostea, kidney, spleen (Neidhardt et al, 2003; Scherberich et al, 2004) and stem cell niches (see below). Tenascin-W is also seen in some adult human periostea (Tucker et al, 2016).…”
Section: Tenascin-w Basicsmentioning
confidence: 99%
“…Consequently, scientists in computational fields have tried to unfold the riddle of Soret effect mechanism in molecular level via molecular dynamics (MD) methods. [34][35][36][37][38] MD techniques can be categorized into two main types: equilibriummolecular dynamics (EMD), [39] and non-equilibrium-molecular dynamics NEMD. [40] EMD approaches anticipate the transport properties of a system through using the Green Kubo formula in the absence of any agitated fields wherein the dynamic properties are associated with the integral of autocorrelation of flow quantities.…”
Section: Introductionmentioning
confidence: 99%